ANALISIS LAJU PERBAIKAN KONDISI KLINIS PASIEN KANKER PAYUDARA MENGGUNAKAN REGRESI ACCELERATED FAILURE TIME WEIBULL (Studi Kasus: RSUD Tugurejo Semarang) - Darari Rahma Lalita; Sudarno Sudarno; Sugito Sugito (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2019)
Breast cancer is a disease caused by abnormal growth from the body’s cells that’s turned into cancer cells. It can spread to other parts of the body so that it can lead to death. Breast cancer is the highest prevalence of cancer in Indonesian women as well as in Semarang City.In an effort to reduce mortality from breast cancer, an analysis of breast cancer patients in Tugurejo General Hospital Semarang can be done by knowing the factors that influence the rate of improvement of breast cancer patient’s clinical conditions. Survival analysis is one of the statistical methods that can be used, the method for which the outcome variable ofinterest is time until an event occurs. Based on Weibull distributed survival time, this study uses Weibull Accelerated Failure Time (AFT) regression method. Dependent variables used is length of time treated and the independent variables used are age, body mass index, anemiastatus, type of treatment, and congenital diseases. The results showed the factors that influence that improvement of breast cancer patient’s clinical condition are age, body mass index, anemia status, and type of treatment. Keywords: Breast Cancer, Improvement of Breast Cancer Patient’s Clinical Condition, Survival Analysis, Weibull Accelerated Failure Time (AFT) Regression